Factors Associated with Tuberculosis Disease in Kupang City - Wanti Wanti; Titik Respati; Irfan Irfan (Poltekkes Kemenkes Kupang, 2025)
Tuberculosis (TB) is still a major public health problem in the world. It is estimated that one-third of the world's population has been infected with TB germs. Factors that cause TB include knowledge, behavior, home environmental conditions and other factors, where all these factors are interrelated, making the TB problem increasingly complex, prevention and intervention steps that must be taken. For this reason, this study was conducted with the aim of determining the factors that influence the incidence of Tuberculosis in Kupang City. This analytical observational study was conducted with a case-control study design. Kupang City was chosen because TB cases are still high in NTT Province. The study period was June–September 2021 with a sample of cases being TB patients undergoing treatment, namely 75 TB patients and 75 non-TB patients as a control group. Data were collected through direct interviews. Analysis was carried out univariately and bivariately with the chi square test. This study found that factors related to the incidence of tuberculosis were knowledge (p 0.049), smoking behavior and number of cigarettes per day (p 0.000), room density (p 0.035), and room lighting (p 0.0009). Therefore, it is necessary to provide more education to the community about how it is transmitted, how to prevent and how to treat it, as well as counseling about the impact of smoking, especially in relation to the risk of tuberculosis. It is also important to provide counseling on healthy homes, especially by reducing residential density (or increasing the size of the house) and arranging the house so that sunlight can enter the house directly in the morning. Protection is needed against smoke caused by wood and kerosene, especially for breathing and especially tuberculosis.